Biogenic amine neurotransmitters promote eicosanoid production and protein homeostasis. (20th January 2021) - Joshi, Kishore K; Matlack, Tarmie L; Pyonteck, Stephanie; Vora, Mehul; Menzel, Ralph; Rongo, Christopher
Abstract: Metazoans use protein homeostasis (proteostasis) pathways to respond to adverse physiological conditions, changing environment, and aging. The nervous system regulates proteostasis in different tissues, but the mechanism is not understood. Here, we show that Caenorhabditis elegans employs biogenic amine neurotransmitters to regulate ubiquitin proteasome system (UPS) proteostasis in epithelia. Mutants for biogenic amine synthesis show decreased poly‐ubiquitination and turnover of a GFP‐based UPS substrate. Using RNA‐seq and mass spectrometry, we found that biogenic amines promote eicosanoid production from poly‐unsaturated fats (PUFAs) by regulating expression of cytochrome P450 monooxygenases. Mutants for one of these P450s share the same UPS phenotype observed in biogenic amine mutants. The production of n ‐6 eicosanoids is required for UPS substrate turnover, whereas accumulation of n ‐6 eicosanoids accelerates turnover. Our results suggest that sensory neurons secrete biogenic amines to modulate lipid signaling, which in turn activates stress response pathways to maintain UPS proteostasis. SYNOPSIS: Protein homeostasis or proteostasis must respond to adverse physiological or environmental conditions. The Caenorhabditis elegans nervous system uses a signaling axis of biogenic amine neurotransmitters and eicosanoids to promote the ubiquitin proteasome proteostasis pathway in epithelia. The C. elegans nervous system releases biogenic amine neurohormones into the body. Biogenic amines promote the expression of cytochrome P450 monooxygenases. These P450 enzymes synthesize omega‐6 eicosanoids from poly‐unsaturated fatty acids. Omega‐6 eicosanoids promote the turnover of metastable proteins in epithelia by the ubiquitin proteasome system. Abstract : Protein homeostasis or proteostasis must respond to adverse physiological or environmental conditions. The Caenorhabditis elegans nervous system uses a signaling axis of biogenic amine neurotransmitters and eicosanoids to promote the ubiquitin proteasome proteostasis pathway in epithelia.